Analysis of respiratory function and muscle strength of elite judo athletes and sedentary females - Ermis, E.; Yilmaz, A. K.; Mayda, H.; Ermis, A. (Journal of Human Sport & Exercise, 2019)
The purpose of this study is to analyse the respiratory function and muscle strengths of elite female judo athletes and sedentary females. 20 elite female judo athletes (EG) and 20 sedentary healthy females (CG) participated in our study. The subjects` respiratory function tests were conducted in sitting position with spirometry, while the respiratory muscle strength tests were conducted by using intraoral barometry. SPSS 22.0 program was used for statistical analysis. When EG and CG were analysed in terms of respiratory functions, no statistically significant difference was found (p>0.05). However, when MIP* and MEP** values were analysed, it was found statistically that female judo athletes (EG) had much higher results when compared with sedentary females (CG) (*p<0.05, **p<0.01). As a conclusion, it can be seen that elite female judo athletes had stronger respiratory muscles when compared with sedentary females, while their lung capacities were found to be similar. Based on the results of our study, it is thought that by doing extra respiratory muscle and function developing trainings, these parameters influencing performance can be developed in female judo athletes. In addition, our study has the characteristic of a reference in terms of respiratory functions and especially respiratory muscle strength in the branch of judo.